The Cocoanuts [videorecording (DVD)] - Santley, Joseph, 1889-1971; Florey, Robert, 1900-1979; Marx, Groucho, 1890-1977; Marx, Chico, 1887-1961; Marx, Harpo, 1888-1964; Marx, Zeppo, 1901-1979; Dumont, Margaret, 1889-1965 (Universal Studios, 2004)
Classic Marx Brothers comedy with Groucho as a hotel owner, Chico and Harpo as con men and Margaret Dumont as a wealthy matron.